2007
DOI: 10.1007/s00220-007-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

D-Branes, RR-Fields and Duality on Noncommutative Manifolds

Abstract: We develop some of the ingredients needed for string theory on noncommutative spacetimes, proposing an axiomatic formulation of T-duality as well as establishing a very general formula for D-brane charges. This formula is closely related to a noncommutative Grothendieck-Riemann-Roch theorem that is proved here. Our approach relies on a very general form of Poincare duality, which is studied here in detail. Among the technical tools employed are calculations with iterated products in bivariant K-theory and cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(119 citation statements)
references
References 75 publications
(131 reference statements)
2
117
0
Order By: Relevance
“…Theorem 1.7). It is known that under favourable circumstances topological T-duality can be expressed as a KK-equivalence between two separable C * -algebras [3,4]. Thus our results show that in such cases one actually has an isomorphism of noncommutative motives that implements the well-known isomorphism (up to a shift) between the twisted K-theories.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Theorem 1.7). It is known that under favourable circumstances topological T-duality can be expressed as a KK-equivalence between two separable C * -algebras [3,4]. Thus our results show that in such cases one actually has an isomorphism of noncommutative motives that implements the well-known isomorphism (up to a shift) between the twisted K-theories.…”
Section: Introductionsupporting
confidence: 59%
“…This formalism extends to certain infinite dimensional spaces through the use of σ-C * -algebras [43]. In [3,4] the authors extended the formalism of T-duality to C * -algebras and showed that under favourable circumstances if B and B ′ are T-dual C * -algebras, then there is an invertible element in KK 0 (B, ΣB ′ ) that implements the twisted K-theory isomorphism (as in (2)). The Connes-Skandalis picture of KK-theory [12] and Rieffel's imprimitivity result [50] are pertinent to their construction.…”
Section: Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denote by D the equivariant Dirac operator constructed by the authors in [3]. In section 4, we prove that there is no operator other than the scalars in the commutant of π(C(SU q (2))) that has bounded commutator with D. An important consequence of this is that the equivariant spectral triple does not give a K-homology fundamental class for SU q (2). In the final section, we show that Poincaré duality holds for SU q (2).…”
Section: Introductionmentioning
confidence: 93%
“…In an earlier paper ( [3]), the authors constructed an equivariant spectral triple for the quantum SU (2) group that was later analysed further by Connes in [8]. It is natural to ask whether the triple gives rise to a fundamental class for SU q (2). This is what we try to answer in this paper.…”
Section: Introductionmentioning
confidence: 94%